Outcomes after 8 years of eliglustat therapy for Gaucher disease type 1: Final results from the Phase 2 trial. Issue 1 (26th October 2018) - Lukina, Elena; Watman, Nora; Dragosky, Marta; Lau, Heather; Avila Arreguin, Elsa; Rosenbaum, Hanna; Zimran, Ari; Foster, Meredith C.; Gaemers, Sebastiaan J. M.; Peterschmitt, M. Judith
Abstract: Eliglustat is a first‐line oral therapy for adults with Gaucher disease type 1 (GD1) and poor, intermediate or extensive CYP2D6‐metabolizer phenotypes (>90% of patients). We report the final results of a Phase 2 trial and extension (NCT00358150) in previously untreated adult GD1 patients who had splenomegaly with thrombocytopenia and/or anemia and received 50 or 100 mg eliglustat tartrate (equivalent to 42 or 84 mg eliglustat) twice daily for 8 years. In total, 19 of 26 patients completed the trial. After 8 years of eliglustat, mean spleen and liver volumes decreased by 69% and 34%, respectively. Mean hemoglobin concentration and platelet count increased by 2.2 g/dL and 113%, respectively. All patients met at least 3 of 4 therapeutic goals established for patients on long‐term enzyme replacement therapy. Mean final values for patients with severe splenomegaly ( n = 6), moderate‐to‐severe anemia ( n = 6), or severe thrombocytopenia ( n = 8) were similar to patients with milder disease at baseline and within long‐term therapeutic goal thresholds. Biomarker median percent changes from baseline were ‐91% for chitotriosidase, ‐87% for CCL18, ‐92% for glucosylsphingosine, and ‐80% for plasma glucosylceramide. Mean lumbar spine T‐score increased by 0.96, moving from the osteopenic to the normal range. Mean quality‐of‐life scores, mostly below normal at baseline, moved into ranges seen in healthy adults. Eliglustat was well‐tolerated; 98% of adverse events were mild or moderate and 94% were considered unrelated to treatment. Clinically meaningful improvements in all parameters continued or were maintained over 8 years, with the largest margins of improvement seen in the most severely affected patients.